New Mathematical Model for the COVID-19 model in Wasit Province - Somaya Saad Faisal; Esam A. Alnussairy (Genius Journals, 2023)
Coronavirus disease 2019 (COVID-19) is a new viral disease that affected multiple organs in the body. Patients infected with SARS-CoV-2 develop arterial thrombosis including stroke, myocardial infarction and peripheral arterial thrombosis. The world wide spread of Covid-19 epidemic has instigated an unprecedented demand and supply of research related to this epidemic.nbsp;
Keywords: COVID-19; pandemic; mathematical modeling